Dual TCRα expression poses an autoimmune hazard by limiting T(reg) cell generation - Schuldt, Nathaniel J. (J Immunol, 2017)
Despite accounting for 10–30% of the T cell population in mice and humans, the role of dual TCR-expressing T cells in immunity remains poorly understood. It has been hypothesized that dual TCR T cells pose an “autoimmune hazard” by allowing self-reactive TCRs to escape thymic selection. We revisited this hypothesis using the NOD murine model of type 1 diabetes (T1D). We bred NOD mice hemizygous at both TCRα and β (TCRα(+/−) β(+/−)) loci, rendering them incapable of producing dual TCR T cells. We found that the lack of dual TCRα expression skewed the insulin-specific thymocyte population toward greater regulatory T (T(reg)) cell commitment, resulting in a more tolerogenic T(reg) to conventional T (T(conv)) cell ratio and protection from diabetes. These data support a novel hypothesis by which dual TCR expression can promote autoimmunity by limiting agonist selection of self-reactive thymocytes into the T(reg) cell lineage.